Resumptive Evaluation of Investment Project Efficiency - Simanauskas, Leonas; Šidlauskas, Skirmantas (Ekonomika, 2006)
The article deals with the problems of evaluating the efficiency of investment projects, attention being on the evaluation of investment projects financed from EU structural funds, illustrating that it is very complicated to evaluate projects by using separate efficiency criteria and that to find the generalizing indicator, criteria of different aspects are required. The evaluation of investment projects should be based on economic, social and environmental criteria selected and grouped taking into account the objectives of EU support assignation. As an example, the applicability of the proposed method in analysing EU financed projects is shown, and it is proven that this method provides a correct and objective picture (efficiency) of the projects.